A challenging diagnosis of MPO-C-ANCA EGPA. Issue 7 (10th July 2019) - Lim, Gareth; Lim, Sheryl; Tee, Shang-Ian; Ling, Chai Yiing
Abstract : Eosinophilic granulomatosis with polyangiitis (EGPA) is a multisystemic small-vessel vasculitic disease that can present with positive MPO-P-ANCA (myeloperoxidase–perinuclear–anti-neutrophil cytoplasmic antibody). It is a rare condition that is difficult to diagnose. We present the case of a 64-year-old man with late-onset adult asthma and treated nasopharyngeal carcinoma who initially presented to us with proximal myopathy. Thereafter, he developed a constellation of fleeting symptoms which included rhinosinusitis, mononeuritis multiplex, skin vasculitis and arthritis. Blood investigations showed that he had eosinophilia, and skin biopsy demonstrated dermal vasculitis with eosinophils. He was found to be MPO-C-ANCA positive, and although initially thought to have granulomatosis with polyangiitis, the diagnosis was later revised to EGPA. This case highlights the diagnostic challenges with atypical presentations of EGPA and also presents a rare case of positive MPO-C-ANCA that has never been described in EGPA before.